Mobbing Syndrome as a Personality Disorder: The Consequences of Complicated Socialisation in the Symptoms of Occupational Destruction - Olena F. Yatsyna (Mukachevo State University, 2021)
The relevance of this study is conditioned by the need to identify the key preconditions and causes of increased violence in the workplace to find new methods of combating mobbing at both international and national levels. The purpose of this study is to analyse mobbing as a psychosocial and medical phenomenon, which is logical to consider with the symptoms of professional destruction. The study of mobbing syndrome took place in two stages based on synergetic methodology using such general scientific research methods as analysis, synthesis, comparison, and systematisation. The study identified the specific features of mobbing at the Ukrainian and world level. The authors considered the main causes of mobbing behaviour as a social issue, as a social phenomenon of the organisation, and as a form of collective violence. The study provides reasoning regarding the necessity of studying the mobbing syndrome from the standpoint of psychosocial and medical aspects. The authors analysed fractal dynamics of mobbing formation, presented in somatogenesis, psychogenesis, and sociogenesis. The study presents the main predictors of professional destruction, which include individual-personal, i.e., total control, manipulation, and conflict, etc., and clinical, which include emotional instability, narcissism, steroidism, and more. It is determined that the types of individual's socialisation develop in accordance with the defensive mechanisms that prevail upon restoring one's security. The study considered the specific features of the clinical aspect of personality disorder. The authors provided a general description of the narcissistic type of personality disorder as a structure of mobster. The practical value of this study lies in the interdisciplinary investigation of mobbing syndrome based on psychosocial and methodological factors